Estrategias didácticas basadas en las inteligencias múltiples para la construcción de aprendizajes significativos en los estudiantes. Año lectivo 2022-2023. - Jumbo Campoverde, Cristy Soledad (2023)
In the educational field, the application of the fundamentals of the theory of multiple intelligences gives teachers the opportunity to offer their students a wide variety of teaching strategies, aimed at responding to their individualities. For this reason, the objective of this research was <<To achieve significant learning in students, through the implementation of didactic strategies based on multiple intelligences, which allow strengthening the development of their individual skills and abilities, in the subject of Natural Sciences in Eighth Grade of basic education, in "La Inmaculada", High school, academic year 2022-2023>>. The method used was the inductive one, it began with the direct observation of the problem and after that, through a bibliographic review, to propose alternative solutions to it. It corresponds to a qualitative approach, which allowed the description of particularities such as the limited implementation of differentiated didactic strategies, in the development of the TLP, which prevents attending to the interests and personal preferences of the students. In addition, according to the nature of the information, it corresponds to participatory action research; since both the student researcher and the students were actively involved, from the diagnosis of the problem to the development of the intervention proposal, in order to improve the identified reality. The results showed that the didactic strategies based on multiple intelligences such as storytelling, learning by discovery, auditory memory exercise, among others, implemented through the techniques story reading, mesocosm construction and musical memorama resolution, respectively. They were widely accepted and favored the construction of significant learning in students. It is concluded that the implementation of didactic strategies based on multiple intelligences allows strengthening the development of individual skills and abilities of students, while they manage to build significant learning. Keywords: Multiple intelligences, types of intelligences, individual differences, teaching-learning, pedagogical models.